Libyan War: A Just or Sinful Intervention - Najimdeen, Bakare (Mediterranean Journal of Social Sciences, 2012)
The paper explores the recent invasion of another Muslim state under the auspices of UNSC’s resolution 1973 andshouldered by NATO. The crisis in Libya leading to the invasion demands deeper understanding of the societal foundation of thisNorth African country. It is equally important not to analyze the events in isolation and independent of the unfolding realities inthe Middle East and North Africa (MENA). The Libya crisis is significant because unlike similar uprising in the region, it wassingled out for foreign intervention. Thus, this piece is therefore looking at the invasion with a multifaceted lens by exploringcompeting worldviews on the intervention. This piece will also not fail to identify the possible fallouts of the invasion, keeping inview the opportunists and losers of the intervention. This paper argues that the military intervention in Libya depicts thecontinuous transformation facing the modern state system and more particularly contributes to our understanding of statesovereignty and its alterations.